Flippin’: Contemporary Filipino-American Stand-up Comedy and Abjection as a Tactic of In/exclusion - Maria Rhodora G. Ancheta (Asiatic: IIUM Journal of English Language and Literature, 2022)
The rise of new, multicultural stand-up comics in the United States appears to have created new spaces for the presentation of long-peripheralised ethnic groups in the country. Deploying the observational humour, a signal contribution of American stand-up comedy, the stand-up comedy acts of contemporary Filipino- American comic artists provide a refocusing on Filipinos, on the Philippines, on Filipino migration to the United States, and on Filipino-American hybrid practices. Thus, they grant force and leverage to Filipino-Americans as a potent American ethnic group, especially as we consider the fact that they constitute the second-largest Asian-American group in the US. Based on this background, this paper aims to interrogate the re/de/constructions of the Philippines and Filipino- ness as transnational ideations that are sifted through the performance of these Filipino-American experiences in stand-up comedy across multimedia streams. It will focus on the contemporary stand-up comic act by Jo Koy, currently one of the most ubiquitous and famous of Filipino-American stand-up comics. Thus, to examine the Filipino/Philippines as transnational originary, and Filipino- American-ness as a nexus of these transnational traffics, the paper will use Julia Kristeva’s theory of abjection, supported by John Limon’s adoption and critique of this concept in his reference to stand-up comedy and humour.